Strategi Komunikasi Organisasi - Zamzami, Wili Sahana (Pusdikra Publishing, 2021)
This study aims to determine the definition of organizational communication, the concept of organizational communication strategy, strategic steps in organizational communication. The method used in this research is library research. The result of the research shows that communication strategy is a joint effort made by two interlocutors to agree on meaning. There are three criteria that must be met in a communication strategy, namely first a communicator wants to communicate a meaning to the communicant; second, the communicator believes that the linguistic or sociolinguistic structure that exists in the meaning of the message cannot be clearly captured by the communicant; third, the communicator chooses to avoid communicating the true meaning of the message or trying alternative ways to communicate the meaning of the message. There are four steps in an organizational communication strategy 1) Knowing the audience 2) Determining objectives 3) Formulating messages 4) Determining the method and choosing the media used.